Defining the Function of Industrial Dynamics – Bulgarian Example - Kopeva, Diana; Shterev, Nikolai; Blagoev, Dimitar (Research Papers, 2014)
The definition of industrial dynamics is important from a theoretical and applied perspective due to the relationship of this economic category with a number of other important categories such as sustainable development and industrial growth. However, the literature is still lacking unified concept of industrial dynamics, and hence there are not yet clearly understood of factors influencing the climate of this macroeconomic phenomenon.Therefore, the authors’ review the basic concepts in the literature on the above listed issues (in the first paragraph) and on that basis justify the construction of a function of industrial dynamics (in the second paragraph). Required Information Assurance is given in the third paragraph and statistical verification of industrial dynamics’ function is formulated in the fourth paragraph of the paper. The last, fifth paragraph is an example of the industrial dynamics function’s usage. Finally, some basic conclusions on the issue are drawn.
Keywords: Industrial dynamic; Industrial growth; Production function; Sells function